2019
DOI: 10.32678/loquen.v12i01.1192
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Listening English Pop Songs to Improve Learners' Vocabulary at LKP Nuansa Jaya

Abstract: Improving English vocabulary through listening can be done by using English songs that are liked by learners. Therefore, the objectives of this research are to know whether there is an influence of listening to English songs on learners’ vocabulary at LKP Nuansa Jaya English Course in Jakarta or not and to identify and classify the word classes of six selected English pop songs. This is a quantitative and qualitative descriptive research employed by 15 young learners. There is an influence of listening English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…YouTube delivers audio and visual content to students, allowing them to understand the spoken English they heard while studying the topic and enhancing their language skills. In sort technology assist the learners to improve their listening skill which link to the study conducted by Hendrawaty (2019).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…YouTube delivers audio and visual content to students, allowing them to understand the spoken English they heard while studying the topic and enhancing their language skills. In sort technology assist the learners to improve their listening skill which link to the study conducted by Hendrawaty (2019).…”
Section: Discussionmentioning
confidence: 93%
“…Many previous studies on learning listening skill and YouTube as a language learning tool have been conducted (Karkera & Chamundeshawari, 2018;Fleck, Beckman, Sterns, & Hussey, 2014;Holland, 2016;Hendrawaty, 2019;Nofrika, 2019). Fleck et al (2014) evidenced the use of Youtube in classroom with invaluable tips for teachers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies indicated that similar results that songs were effective enough to improve learners' skills in English including listening, speaking, pronunciation, and also vocabulary (Shen, 2009;Millington, 2011). Likewise, songs are also able to encourage learners to spend more time to learn English that they find them interesting, fun, and tranquil (Kurnierek, 2016;Pratiwi, 2018;Hendrawaty & Nurhayati, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…In addition, the term "listening materials" may be used to refer to anything that is used by teachers to aid students in the process of learning a language during a listening activity. As a consequence of this, the kids need to have access to appropriate listening material (Hendrawaty, 2019;Ujihanti, et. al., 2019) Recent changes made by the government brought the curriculum up to date, moving it from 2006 (KTSP) to curriculum 2013 (K-13).…”
Section: Introductionmentioning
confidence: 99%